Stress‐driven increase in proline levels, and not proline levels themselves, correlates with the ability to withstand excess salt in a group of 17 Italian rice genotypes. (13th October 2018) - Forlani, G.; Bertazzini, M.; Cagnano, G.
Abstract: In most plant species, a rapid increase in free proline content occurs following exposure to hyperosmotic stress conditions. However, inconsistent results were reported concerning the role of such an increase on the plant response to water shortage or excess salt. Therefore, the possibility that proline accumulation may help the cell to withstand stress conditions, or that it simply represents a stress marker, is still a matter of debate. A possible relationship between proline accumulation and salt tolerance was investigated in a set of 17 Italian rice varieties. Rice seedlings were exposed to increasing salt concentrations during germination and early growth. The resulting levels of free proline were measured separately in shoots and roots and compared to those in untreated controls. Results were related to the corresponding ability of a given genotype to tolerate stress conditions. Neither absolute proline levels in untreated or in salt‐stressed seedlings showed a straightforward relationship to the relative tolerance to salt, estimated as conductivity values able to reduce growth by 10 or 50%. Conversely, a highly significant correlation was found between the increase in proline levels in shoots and the ability to withstand stress. The results strengthen a recent hypothesis suggesting than an increase in proline metabolic rates, more than the resulting proline content, may help the cell to counteract the effects of abiotic stress conditions.